Bronchial segmentation of right bronchial tree and its variation: A Bronchoscopic Study - Thapa, Srijana; Thakur, Binay; khatiwada, Sagar; Bhattarai, Shachee; Kharel, Ashish; Adhikari, Mahesh Mani; Sapkota, Sandeep; Shrestha, Laxmi; Paudel, Dipti (Nepalese Journal of Cancer, 2025)
Background: Bronchoscopy is of paramount importance in the field of thoracic surgery. Over the years it has evolved as an important diagnostic and therapeutic tool. The aim of our study was to describe the frequency of right sided segmental bronchial variation identified during bronchoscopy. Methods: A meticulous examination of both right and left bronchial tree was done during bronchoscopy in 60 patients. Indications for bronchoscopy was part of suspected malignancy work up. Segmental as well as the subsegmental bronchi (B1-10) were properly identified. Any accessory bronchus in the tracheobronchial tree was also noted. Results: Our results show that there are no significant differences in the incidence of variations by sex. The highest recorded variations of 80.8% was found in the right lower lobe followed by right upper lobe with frequency of 40.4%whereas RML had no variation. Conclusion: Significant segmental bronchial variations do exist in the general population. Bronchoscopy is also an important tool to delineate and confirm the segmental bronchial variations.